Connexin hemichannel induced vascular leak suggests a new paradigm for cancer therapy. Issue 8 (15th February 2014) - Zhang, Jie; O'Carroll, Simon J.; Henare, Kimiora; Ching, Lai-Ming; Ormonde, Susan; Nicholson, Louise F.B.; Danesh-Meyer, Helen V.; Green, Colin R.
Abstract : It is 40 years since cancer growth was correlated with neovascularisation. Anti‐angiogenic drugs remain at the forefront of cancer investigations but progress has been disappointing and unexpected toxicities are emerging. Gap junction channels are implicated in lesion spread following injury, with channel blockers shown to improve healing; in particular preventing vascular disruption and/or restoring vascular integrity. Here we briefly review connexin roles in vascular leak and endothelial cell death that occurs following acute wounds and during chronic disease, and how connexin channel regulation has been used to ameliorate vascular disruption. We then review chronic inflammatory disorders and trauma in the eye, concluding that vascular disruption under these conditions mimics that seen in tumours, and can be prevented with connexin hemichannel modulation. We apply this knowledge to tumour vessel biology, proposing that contrary to current opinion, these data suggest a need to protect, maintain and/or restore cancer vasculature. This may lead to reduced tumour hypoxia, promote the survival of normal cells, and enable improved therapeutic delivery or more effective radiation therapy.